2021
DOI: 10.1172/jci.insight.143058
|View full text |Cite
|
Sign up to set email alerts
|

Targeted DNA methylation profiling reveals epigenetic signatures in peanut allergy

Abstract: DNA methylation (DNAm) has been shown to play a role in mediating food allergy, however, the mechanism by which it does so is poorly understood. In this study, we used targeted NextGen bisulfite sequencing to evaluate DNAm levels in 125 targeted highly informative genomic regions containing 602 CpG sites on 70 immune-related genes to understand whether DNAm can differentiate peanut allergy (PA) vs non-allergy (NA). We found PA-associated DNAm signatures associated with 12 genes (7 potentially novel to food all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 66 publications
2
48
0
Order By: Relevance
“…Furthermore, a high similarity between peanut allergic-and non-allergic patients was observed in monozygotic twins compared to randomly-paired genetically unrelated individuals. This indicates that 12 DNA methylation signature-associated peanut allergy was genetically influenced [47]. Another study described different DNA methylation profiling in Th1 and Th2 cells comparing non-allergic and peanut allergic patients.…”
Section: Peanut Allergymentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, a high similarity between peanut allergic-and non-allergic patients was observed in monozygotic twins compared to randomly-paired genetically unrelated individuals. This indicates that 12 DNA methylation signature-associated peanut allergy was genetically influenced [47]. Another study described different DNA methylation profiling in Th1 and Th2 cells comparing non-allergic and peanut allergic patients.…”
Section: Peanut Allergymentioning
confidence: 97%
“…The study suggested that the HLA-DR and -DQ gene region likely poses a significant genetic risk for peanut allergy [46]. Another study revealed that DNA methylation profiling on PBMCs from peanut allergic and non-allergic patients in 96 CpG sites, predicting clinical outcomes [47]. They determined several potential new genes associated with peanut allergy, such as BDNF (neurotrophin) and SERPINE1 (serine protease inhibitor), showing a new research line to elucidate the molecular basis of peanut allergy.…”
Section: Peanut Allergymentioning
confidence: 99%
“…This indicates a better diagnostic biomarker in comparison to serum IgE. However, there are a variety of responses between peanut allergy and no allergy samples that could indicate the interaction of these genes with the environmental factors [69].…”
Section: Dna Methylation Affects Gene Expression In the Presence Of Food Allergensmentioning
confidence: 98%
“…The latest next-generation bisulfite sequencing allows greater coverage of each CpG site at promoter/enhancer regions at genes of interest. This technique has evidently evaluated DNA methylation levels on 70 immune-related genes to address the association between methylation at the CpG sites of these genes to the response of peanut allergen [69]. In peanut allergy, 12 genes were hypermethylated, of which 7 of those were potentially novel to food allergy, 3 genes were associated with Th1/Th2 responses, and 2 genes were associated with innate immunity [69].…”
Section: Dna Methylation Affects Gene Expression In the Presence Of Food Allergensmentioning
confidence: 99%
See 1 more Smart Citation